1972
DOI: 10.1097/00006254-197206000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variation in Menstrual Blood Loss

Abstract: Menstrual blood losses were measured in 348 women aged 17 to 45 years in a Northumbrian mining village. Menstrual loss was found to be related to parity and to the birthweight of previous children. It is possibly associated with height, and may be partly controlled by uterine size and blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Furthermore, several studies have reported a significant inverse correlation between Fe stores and the duration of menstruation (49)(50)(51) . In addition, a number of studies in European women have shown a skewed distribution in menstrual blood losses (49,(52)(53)(54) : while median menstrual loss was about 30 ml, equivalent to a daily Fe loss of 0?45 mg, 25 % had a loss exceeding 0?85 mg/d and 5 % had a loss exceeding 1?75 mg/d. It is suggested that a fraction of women have Fe requirements substantially above mean values.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have reported a significant inverse correlation between Fe stores and the duration of menstruation (49)(50)(51) . In addition, a number of studies in European women have shown a skewed distribution in menstrual blood losses (49,(52)(53)(54) : while median menstrual loss was about 30 ml, equivalent to a daily Fe loss of 0?45 mg, 25 % had a loss exceeding 0?85 mg/d and 5 % had a loss exceeding 1?75 mg/d. It is suggested that a fraction of women have Fe requirements substantially above mean values.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that blood loss could range from a few millilitres to 400 ml per period. There is a marked variation in menstrual blood loss between different women 28,29 , but it is relatively constant in an individual woman throughout fertile life 26 . Since this time, the increased use of oral contraceptives may have reduced average blood losses and hence iron requirements 30 .…”
Section: Considerations Of Assumptions Made In Our Studymentioning
confidence: 99%
“…The average blood loss in a Caucasian female population is approximately 30-40 millilitres per menstrual flow (Cole et al 1971;Hallberg et al 1966), the majority of which is lost in the first forty eight hours. Menorrhagia is the commonest cause of iron deficiency anaemia in women in the developed world and occurs in sixty per cent of women with objective menorrhagia.…”
Section: Menorrhagiamentioning
confidence: 99%